Correction to: Vaccination with nanoparticles combined with micro-adjuvants protects against cancer. Issue 1 (23rd May 2019) - Mohsen, Mona O.; Heath, Matthew D.; Cabral-Miranda, Gustavo; Lipp, Cyrill; Zeltins, Andris; Sande, Marcos; Stein, Jens V.; Riether, Carsten; Roesti, Elisa; Zha, Lisha; Engeroff, Paul; El-Turabi, Aadil; et al.
Abstract : Following publication of the original article [1], the author reported an author's family name has been misspelled. Paul Engroff should be replace Paul Engeroff. Furthermore, there are two mistake in two affiliations: 9) Department of dermatology, University of Zurich, Bern, Switzerland and 10) Department of Oncology, University of Lausanne, Bern, Switzerland should be replace with 9) Department of dermatology, University of Zurich, Zurich, Switzerland. 10) Department of Oncology, University of Lausanne, Lausanne, Switzerland.